Dissemination of exposure in the treatment of anxiety disorders and post‐traumatic stress disorder among German cognitive behavioural therapists. (17th August 2018) - Schumacher, Sarah; Weiss, Deborah; Knaevelsrud, Christine
Abstract: The efficacy of exposure is beyond doubt, which is reflected in guidelines recommending its application in the treatment of anxiety disorders and post‐traumatic stress disorder (PTSD). Research suggests exposure to be underutilized in clinical practice in the United States and Europe. A systematic investigation of the dissemination of exposure in Germany is lacking. The present study examined the dissemination and application frequency of exposure among German cognitive behavioural therapists working in routine care. In an online‐based survey, 331 psychotherapists provided information on treatment of patients with panic disorder, phobia, and PTSD. By means of multinomial logistic regression analysis, application frequency of exposure ( non‐users vs . users vs . frequent users ) was predicted by various therapist characteristics. Younger age and less negative beliefs about exposure significantly predicted the affiliation to the frequent users group compared to the non‐users in the treatment of panic disorder or phobia. Concerning treatment of PTSD, only negative beliefs about exposure was identified as significant predictor. Sex, educational level, and number of exposure sessions performed during clinical training were not of predictive value. Current findings suggest that negative beliefs about exposure and age impact the frequent provision of exposure to patients. Modification of negative attitudes might be achieved through specific training strategies.